African Hydroclimate During the Early Eocene From the DeepMIP Simulations. Issue 5 (16th May 2022) - Williams, Charles J. R.; Lunt, Daniel J.; Salzmann, Ulrich; Reichgelt, Tammo; Inglis, Gordon N.; Greenwood, David R.; Chan, Wing‐Le; Abe‐Ouchi, Ayako; Donnadieu, Yannick; Hutchinson, David K.; de Boer, Agatha M.; Ladant, Jean‐Baptiste; et al.
Abstract: The early Eocene (∼56–48 Myr ago) is characterized by high CO2 estimates (1, 200–2, 500 ppmv) and elevated global temperatures (∼10°C–16°C higher than modern). However, the response of the hydrological cycle during the early Eocene is poorly constrained, especially in regions with sparse data coverage (e.g., Africa). Here, we present a study of African hydroclimate during the early Eocene, as simulated by an ensemble of state‐of‐the‐art climate models in the Deep‐time Model Intercomparison Project (DeepMIP). A comparison between the DeepMIP pre‐industrial simulations and modern observations suggests that model biases are model‐ and geographically dependent, however, these biases are reduced in the model ensemble mean. A comparison between the Eocene simulations and the pre‐industrial suggests that there is no obvious wetting or drying trend as the CO2 increases. The results suggest that changes to the land sea mask (relative to modern) in the models may be responsible for the simulated increases in precipitation to the north of Eocene Africa. There is an increase in precipitation over equatorial and West Africa and associated drying over northern Africa as CO2 rises. There are also important dynamical changes, with evidence that anticyclonic low‐level circulation is replaced by increased south‐westerly flow at high CO2 levels. Lastly, a model‐data comparison using newly compiled quantitative climate estimates from paleobotanical proxy data suggests a marginally better fit with the reconstructions at lower levels of CO2 . Plain Language Summary: Approximately 50 Myr ago, a period known as the early Eocene, atmospheric carbon dioxide levels were significantly higher than today, and were more similar to what they could be in the future, if efforts to reduce human greenhouse gas emissions are unsuccessful. However, rainfall changes during this period are less well understood, especially over data‐sparse regions such as Africa. Here, a collection of state‐of‐the‐art climate models are used to study African rainfall during this period, comparing the simulations first to present‐day African rainfall (to validate the models), second to varying levels of atmospheric carbon dioxide, and lastly to newly compiled reconstructions of early Eocene rainfall (from plant fossils). The main findings are that although the models can reproduce present‐day rainfall over Africa, and compare reasonably well with the reconstructions, there is no clear rainfall signal when atmospheric carbon dioxide is increased. Nevertheless, the combination of a different continental configuration, vegetation, topography, and atmospheric carbon dioxide leads to changing rainfall patterns, connected to temperature and low‐level wind changes. Key Points: State‐of‐the‐art climate models are used to study African hydroclimate during the early Eocene (approximately 50 Myr ago) With increasing levels of CO2, there are changes to African precipitation, due to dynamical changes such as low‐level circulation A comparison between the models and newly compiled climate estimates shows a marginally better match at lower levels of CO2